Case Report: Prenatal ultrasound presentation of congenital melanocytic nevus syndrome - Shi, ZhiH; Sun, TingT; Yin, Juan; Qiu, Shuo; Wang, YueM; Leng, JunH (Frontiers in Pediatrics, 2024)
Congenital melanocytic nevus (CMN) syndrome is a rare, non-familial neural ectodermal dysplasia characterized by CMN combined with extracutaneous abnormalities, predominantly involving the central nervous system (CNS). The pathogenesis of CMN syndrome is thought to result from early post-zygotic somatic mutations. CNS melanosis frequently affects the anterior temporal lobes, brainstem, cerebellum, and cerebral cortex. Magnetic resonance imaging typically demonstrates T1 hyperintensity associated with CNS melanosis, while ultrasound often reveals abnormal echogenicity. We report a case of a fetus diagnosed with CMN syndrome, presenting with abnormal echogenicity in the cerebellar and amygdaloid complexes and a posterior fossa cyst. Autopsy identified two melanocytic nevi on the lumbosacral region of the fetus. Reports linking CMN syndrome to fetal intracranial abnormalities remain exceedingly rare.